Formulasi Limbah Cangkang Telur Ayam Ras Dengan Kompos Limbah Pasar untuk Peningkatan Hasil Sawi Hijau (Brassica juncea L.) - SUPADMA, A.A. NYOMAN; DANA, I MADE; ARTHAGAMA, I DEWA MADE (Agrotrop : Journal on Agriculture Science, 2022)
The formulation of chicken eggshell waste with market waste compost to increase the yield of green mustard ( Brassica juncea L.) . Aims to find the best and environmentally friendly organic fertilizer formula to increase the yield of green mustard and improve some soil chemical properties. This research is a pot experiment in a greenhouse, using a simple randomized block design consisting of 7 combinations. Fertilizer formulas that were tried were: F0 (without treatment), F1 = (100 kg of shell + 10 tonnes of compost), F2 = (200 kg of shell + 8 tonnes of compost), F3 = (300 kg of shell + 6 tonnes of compost), F4 = (400 kg of shell + 4 tons of compost), F5 = (500 kg of shells + 2 tons of compost), F6 = (600 kg of shells + 0 tons of compost), and each treatment was repeated 4 times. The parameters observed included: maximum plant height (cm), fresh plant weight at harvest, oven dry plant weight, soil pH, C-organic content, CEC and soil Ca content at harvest. The data were analyzed statistically, tested for variance. If the effect of the treatment had significant, then continued with the 5 % Duncans test. The results of this study indicate that the treatment has a significant effect on plant height growth, fresh weight and oven dry weight of plants, as well as changes in soil chemical properties such as: C-organic, soil CEC, and soil Ca content. The fresh plant weight was obtained in treatment F2 (9.55 g), followed by F3 (9.37 g), and F1 (9.18 g) per pot. While the highest CEC was obtained in the F2 treatment (36.31 me 100 g -1 ) with a soil Ca content of 7.52 me 100 g -1 . The best fertilizer formula from this study was found in the F2 treatment.